تمارين صولفائية مستنبطة من بعض الجمل اللحنية للأغاني عند زياد الرحباني - محمد، فاطمة عصام عبدالمقصود (جامعة حلوان - كلية التربية الموسيقية, 2020)
الأغنية هي قالب يتميز بمجموعة من الخصائص الفنية والتي تجعله مختلفة عن غيره من القوالب الغنائية، وبرع في قالب الأغنية العديد من الملحنين وأظهروا إبداعاتهم التلحينية، ونخص بالذكر الملحن زياد الرحباني، فهو يعد أحد ملحني الأغنية العربية الحديثة، وتميز أسلوبه اللحني بالتجديد وإظهار الأغنية بشكل مختلف عن المألوف، وتطورت الأغنية على يديه بشكل كبير. كما هدف البحث إلى التعرف على بعض أعمال زياد الرحباني الغنائية والاستفادة منها في تحسين مستوى أداء الطلاب في مادة الصولفيج والغناء العربي، ويتضمن البحث جزئين: أولا: الإطار النظري ويشمل (مفهوم الصولفيج بشكل عام - مفهوم الصولفيج العربي- مفهوم الأغنية العربية - مفهوم القصيدة - نبذة عن الفنان زياد الرحباني ونشأته وأعماله الموسيقية). ثانيا: الإطار التطبيقي ويشمل (المقام الخاص بأغنية ع هدير البوسطة - الجمل اللحنية لأغنية ع هدير البوسطة بالإضافة إلى التمارين المستوحاة منها والمهارات التي يحتوي عليها كل تمرين - المقام الخاص بأغنية كيفك إنت - الجمل اللحنية لأغنية كيفك إنت بالإضافة إلى التمارين المستوحاة منها والمهارات التي يحتوي عليها كل تمرين). واختتمت الباحثة هذا البحث بالنتائج والتوصيات المقترحة ثم مراجع البحث ثم مخلص البحث باللغة العربية واللغة الإنجليزية.
The song is a template that is distinguished by a group of artistic characteristics that make it different from other lyric templates. Many composers excelled in the song template and showed their compositional creations. Specifically, the composer Ziad Al-Rahbani is considered one of the curves of the modern Arabic song, and his style is characterized by the brightness of renewal and the presentation of the song in a different way On the familiar, the song developed greatly on his hands. The research also aimed to identify some of Ziad Al-Rahbani’s lyric work and benefit from it in improving the level of students ’performance in solfege and Arabic singing. The research includes two parts: First: the theoretical framework includes (the concept of Solfege in general - the concept of the Arab Solfege - the concept of the Arabic song - The concept of the poem - a brief summary of the biography of the artist Ziad Al-Rahbani, his genesis and his musical works). Second: The practical framework includes (the maqam for the song a hadeer el posta - melodic phrases of the song a hadeer el posta and the exercises inspired from it and the skills contained in each exercise - the maqam for the song keifak enta - melodic phrases of the song keifak enta and the exercises inspired from it and the skills contained in each exercise. The researcher concluded this research with the proposed results and recommendations, then the research references, then the research summary in Arabic and English.
Keywords: الموسيقى العربية -- الغناء العربي -- الصولفيج -- الرحباني، زياد -- النقد الفني